Psychosocial and community assessment of relatives of victims of extra-judicial killings in Peru: Informing international courts - Rivera-Holguín, Miryam; Pérez-Sales, Pau; Hildenbrand, Adriana; Custodio, Elba; Vargas, Germán; Baca, Nelida; Corveleyn, Jozef; De Haene, Lucia (Torture Journal, 2019)
Introduction: During the Peruvian internal armed conflict, fifteen members of the Santa Barbara community were collectively executed by state agents, and their relatives were made victims of persecution, torture, and imprisonment. The case, known as the Santa Barbara massacre, was brought to the Inter-American Court of Human Rights. The documentation of individual, family and community impacts for the Court became a challenge due to the need to address cultural, geographical, political and community aspects. This paper aims to discuss the complexities of forensic documentation of human rights violations using a psychosocial and communitarian background. Method: The assessment included seven survivors from three different families. Both qualitative and quantitative instruments were used. A participative action research framework guided the design, documentation process, and discussion of outcomes with the survivors. Results/ discussion: The report included four levels of documentation exhibited in the Istanbul Protocol framework: clinical impacts from a western perspective, emic formulations and cultural idioms of distress, communitarian perspectives, and a proposal of reparation measures for the Court. Individual analysis revealed chronic mental health sequelae of forced displacement, imprisonment and torture. Local idioms of distress (in Quechuan, “pinsamientuwan,” “llaki,” “ñakary,” “umananay” and “iquyay”) deepened the understanding of the damage faced by the survivors. The analysis of the community uncovered three main areas of collective damage: broken social and cultural identity, lack of political participation, and loss of perspective on the future. Regarding reparations, survivors highlighted the pursuit for justice, the dignified remembrance of their loved ones, social re-inclusion of displaced persons into the community, education for offspring, and measures for the preservation of their community’s identity and culture. Conclusions: Psycholegal accompaniment for victims through a participatory research approach is essential for the proper documentation of the consequences of violence in complex contexts. It is also essential in guaranteeing that the forensic documentation of the impact of political violence can be proposed as reparative for the survivors in itself.